The Kazakh diaspora in Central Asia: preservation of national identity and institutional influence in the region - Nurbek, Kuralay; Kalashnikova, Natalya; Turan, Ugur (Frontiers in Political Science, 2025)
IntroductionThe aim of this study is to characterize the migration interaction between Kazakhstan and the Central Asian countries, as well as the Kazakh diaspora within them. To achieve this objective, key aspects of Kazakhstan’s new migration policy, as reflected in national legislation, were identified, as well as gaps in the new Migration Policy Concept of Kazakhstan.MethodsUsing statistical data from national statistical institutions, the World Bank, and the “Otandastar Fund” Society, the Kazakh diaspora was characterized in terms of its quantitative representation in each of the Central Asian countries. The relationship between the diaspora and the national population, as well as other diasporas, was analyzed, including the proportion of the Kazakh diaspora within the regional (Central Asian countries) and global context. Based on the analysis of official information from Kazakhstan’s diplomatic missions, the main areas of work with the Kazakh diaspora in each of the countries in the region were identified.Results and discussionIt was shown that, despite a significant historical, ethnic, and mental commonality, migration processes between Kazakhstan and each of the Central Asian countries have their peculiarities. The activities of the diasporas and the organization of their interaction with the country of origin also have significant differences, as do the reasons for the decline in the Kazakh diaspora’s numbers in certain Central Asian countries. The modern development of international relations necessitates a revision of the concept of diaspora by adding additional characteristics to the ethnic component, allowing people from one country of origin to unite not only based on co-residence in another state but also through non-territorial association aimed at supporting the country of origin, particularly in scientific, business, economics and socially useful interests. The results of this study can form the basis for national laws, concepts, and programs in the field of migration and cooperation with the Kazakh diaspora in the Central Asian region, as well as for practical activities in this area.